Intracellular re-routing of prion protein prevents propagation of PrP(Sc) and delays onset of prion disease - Gilch, Sabine (Oxford University Press, 2001)
Prion diseases are fatal and transmissible neurodegenerative disorders linked to an aberrant conformation of the cellular prion protein (PrP(c)). We show that the chemical compound Suramin induced aggregation of PrP in a post-ER/Golgi compartment and prevented further trafficking of PrP(c) to the outer leaflet of the plasma membrane. Instead, misfolded PrP was efficiently re-routed to acidic compartments for intracellular degradation. In contrast to PrP(Sc) in prion-infected cells, PrP aggregates formed in the presence of Suramin did not accumulate, were entirely sensitive to proteolytic digestion, had distinct biophysical properties, and were not infectious. The prophylactic potential of Suramin-induced intracellular re-routing was tested in mice. After intraperitoneal infection with scrapie prions, peripheral application of Suramin around the time of inoculation significantly delayed onset of prion disease. Our data reveal a novel quality control mechanism for misfolded PrP isoforms and introduce a new molecular mechanism for anti-prion compounds.